Development of a decision model for selecting action plans in EFQM - Dodangeh, Javad; Mohd Yusuff, Rosnah (IEEE, 2013)
In a progressively turbulent and competitive business environment, numerous organizations adopt the total quality management (TQM) approach to endeavor for business excellence; in this sense total quality management (TQM) and excellence frameworks play vital roles in organizational successes and sustainable business. Thousands of firms beyond the globe use self-assessment system in a regular manner to monitor the progress towards business excellence. There are a few popular business excellence models that provide standard criteria against which an organization can measure its performances. European Foundation for Quality Management (EFQM) is the most popular ones. Currently, it is the most widely employed as an organizational assessment model in Europe and across the globe and become the basis for the majority of international, national and regional quality awards. Nevertheless, the current EFQM model has some drawbacks, which are not able to recognize the preferences in Area for Improvement (AFI). Companies cannot be able to implement all the Area for Improvement due to constraints of time, budget and resources, etc. some criteria would be delineated for ranking and choosing the AFI. The proposed model is designed in order to develop a multi criteria decision making method using simple additive weighting (SAW) to consider multi criteria for selecting AFIs in EFQM in terms of expert panel opinions. The model was tested and verified under real condition and were implemented in a mega car producing company. The case was assessed by assessors and experts of an EFQM business excellence organization and internal assessors of the companies. Furthermore, by analysing of classic and new model, assessors and experts agreed with outputs of the developed model.